Geography Teachers' Competence in Utilizing Learning Resources at SMA Negeri 15 Central Maluku - Wattiheluw, Suria; Leuwol, Ferdinand Salomo; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Education has become a crucial pillar in human civilization, ensuring the transmission of knowledge, skills, and values from one generation to the next, ensuring the continuity and progress of society. With an anticipatory and preparatory approach, ideal education prepares the younger generation to face the future with critical thinking, innovation, and adaptability to change. The utilization of learning resources in SMA Negeri 15 Maluku Tengah still needs to be improved, influenced by the lack of teacher competence in effectively utilizing various learning resources. Although teaching resources such as textbooks, digital media, and practical experiences are available, the lack of teacher skills in integrating them into teaching reduces the effectiveness of education. Enhancing teacher competence in resource utilization strategies is essential to improve the quality of education in the school. This research employs a phenomenological approach to understand the meaning of interactions in specific situations, focusing on the competence of geography teachers in utilizing learning resources in SMA Negeri 15 Maluku Tengah. This qualitative descriptive study analyzes the availability and utilization of various learning resources and their impact on learning. The results will likely provide a deep understanding of effective strategies to enhance teachers' utilization of learning resources, thereby improving the quality of education in the school. Teachers at SMA Negeri 15 Maluku Tengah utilize various learning resources in geography lessons, including conventional media and additional ones like newspapers, videos, and the internet. However, the use of digital media still needs to be improved, although they demonstrate creativity in teaching methods and adaptation to student characteristics. Further integration of digital media can enrich students' learning experiences and prepare them for the digital era.